Analysis of blood utilization in programmed surgery. - Oliveira, A; Fleming, R; Galvão, M (Acta Médica Portuguesa, 1997)
The purpose of this study is to analyse the crossmatched blood units for elective surgery and the real amount of transfused blood, the crossmatch:transfusion rate (C:T) which must be less than 2.5. As in other Blood Banks, the differences are more evident in the situations in which the need for blood is very small, the so called "Type and Screen".